(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Dental caries remains one of the most prevalent chronic diseases worldwide, affecting approximately 2.3 billion individuals. Despite preventive strategies, early detection and optimal management continue to present clinical challenges. Traditional diagnostic methods often identify carious lesions at advanced stages, necessitating invasive restorative interventions. In recent decades, significant technological advances have transformed caries detection and treatment paradigms. Modern diagnostic tools—including digital radiography, laser fluorescence devices, quantitative light-induced fluorescence (QLF), optical coherence tomography (OCT), and artificial intelligence (AI)–based systems—have enhanced early detection accuracy. Simultaneously, treatment strategies have shifted toward minimally invasive dentistry, emphasizing remineralization, bioactive restorative materials, and tissue preservation. This article reviews contemporary diagnostic technologies and therapeutic approaches in dental caries management, highlighting their clinical relevance and future perspectives.